2016
DOI: 10.1159/000443188
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Saliva Formulations versus Human Saliva Pretreatment in Dental Erosion Experiments

Abstract: The aim of this study was to evaluate the erosion-preventive effect of different artificial saliva formulations and human saliva in vitro compared to human saliva in situ. In the in vitro experiment, bovine enamel and dentin specimens were stored in artificial saliva (4 different formulations, each n = 20), deionized water (n = 20) or human saliva (n = 6 enamel and dentin specimens/volunteer) for 120 min. In the in situ experiment, each of the 6 enamel and dentin specimens was worn intraorally by 10 volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 82 publications
1
24
0
5
Order By: Relevance
“…A more recent study has demonstrated that, while the hardness loss was not different, the calcium release during erosion can differ between (bovine) enamel covered with an in situ or an in vitro formed pellicle. The authors concluded that the use of saliva in vitro does not adequately reflect in situ conditions in the erosion model they used [Batista et al, 2016]. But generally, while in situ results do not fully match quantitatively with in vitro results, they usually follow the same trend [West et al, 2011].…”
Section: Discussionmentioning
confidence: 97%
“…A more recent study has demonstrated that, while the hardness loss was not different, the calcium release during erosion can differ between (bovine) enamel covered with an in situ or an in vitro formed pellicle. The authors concluded that the use of saliva in vitro does not adequately reflect in situ conditions in the erosion model they used [Batista et al, 2016]. But generally, while in situ results do not fully match quantitatively with in vitro results, they usually follow the same trend [West et al, 2011].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is plausible to attribute the differences of ΔGU1, ΔL1, Δa1, and Δb1 between the groups to a possible protection against erosion offered in the less affected groups. However, Batista et al 30 excluded such an erosion‐protective effect for various formulas of artificial saliva as those were not able to build a protective pellicle layer on the enamel. On the other hand, Baumann et al 31 found artificial saliva to have a certain erosion‐protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…They attributed this protective effect to the presence of sodium and chloride ions which suppressed the dissolution of hydroxyapatite. It should be mentioned that the erosive attack was undertaken differently in each of the abovementioned studies (hydrochloric acid pH 2.6/1 minute 30 and citric acid pH 3.6/1 minute 31 ). Eventually, it remains unclear whether the artificial saliva used in this study could after all offer some kind of erosion protection and thus alter the susceptibility to color adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…No que diz respeito ao tipo de estudo, apesar de os experimentos in vitro ainda prevalecem nas investigações sobre erosão dentária, provavelmente por serem financeiramente mais viáveis e permitirem uma avaliação rápida de produtos/tratamentos 52 , os mesmos não são capazes de reproduzir as características biológicas inerentes ao ambiente bucal.…”
Section: Discussionunclassified